Russulaceae of the Pakaraima Mountains of Guyana 5. Two newly described diminutive species in a novel lineage of the crown clade of Russula (Russulaceae) - Miller, Steven L.; Aime, M. Catherine; Henkel, Terry W. (Phytotaxa, 2024)
Much of our previous work documenting fungal biodiversity in Guyana has been centered in forests of Dicymbe corymbosa Spruce ex Benth., which forms monodominant stands in the white sands region of Guyana. In order to begin to assess fungal biodiversity associated with other ectomycorrhizal host trees found in Guyana, expeditions were conducted to areas containing Dicymbe altsonii and Pakaraimaea dipterocarpacea. In this paper, we describe two new species of Russula from Guyana with diminutive basidiomata: R. lilliputia and R. pakaraimaeae, found in association with these tree hosts, using a combined approach of morphological characterization and molecular analyses. Together with R. gelatinivelata, which we previously described from Guyana, R. lilliputia and R. pakaraimaeae form what appears to be a new lineage within the crown clade of Russula, sister to the subsect. Auratinae. Synapomorphies for the lineage include a pruinose to subtomentose pileus in dry conditions, suprapellis comprised of inflated cells that give rise to long cylindrical or digitate, and sinuous, thin or thick-walled pileocystidia that are strongly emergent, easily disarticulate in microscopic preparations, and have contents that are acid resistant in Basic Fuchsin, pruinose to subomentose patches on the stipe, suprahilar plage on the basidiospores, spore ornamentation of mostly isolated verrucae, and geographic distribution restricted to the Pakaraima Mountains of Guyana. Full descriptions, photos, line drawings of microscopic features, and comparisons with related species are provided.